2015
DOI: 10.1111/boj.12249
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite markers indicate genetic differences between cultivated and natural populations of endangeredTaxus yunnanensis

Abstract: Taxus yunnanensis (Taxaceae) is an endangered plant known for its effective natural anti-cancer metabolite, taxol. To assess the effectiveness of T. yunnanensis ex situ conservation in China, the genetic diversity and genetic structure of nine cultivated and 14 natural populations were compared using 11 polymorphic microsatellite markers. The purpose of this comparison was to determine whether the cultivated populations were genetic representatives of natural types. Among the 14 natural populations studied, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…3). Because of the small population sizes, increased spatial isolation, and artificial selection caused by incomplete sampling strategies, high levels of ex-situ-wild F ST have been reported in several empirical studies, even between ex situ populations and the wild populations where they were collected (Lauterbach et al 2012;Miao et al 2015;Müller et al 2017). Furthermore, the effect size of ex-situwild F ST significantly increased as the duration of ex situ conservation increased (Fig.…”
Section: Higher Genetic Differentiation Between Ex Situ and Wild Popumentioning
confidence: 95%
See 1 more Smart Citation
“…3). Because of the small population sizes, increased spatial isolation, and artificial selection caused by incomplete sampling strategies, high levels of ex-situ-wild F ST have been reported in several empirical studies, even between ex situ populations and the wild populations where they were collected (Lauterbach et al 2012;Miao et al 2015;Müller et al 2017). Furthermore, the effect size of ex-situwild F ST significantly increased as the duration of ex situ conservation increased (Fig.…”
Section: Higher Genetic Differentiation Between Ex Situ and Wild Popumentioning
confidence: 95%
“…Inbreeding coefficient also exhibits mixed results among ex situ conservation genetic studies (Aavik et al 2012;Yokogawa et al 2013). Furthermore, the levels of genetic differentiation among ex situ populations (among-ex-situ F ST ) or between ex situ and wild populations (ex-situ-wild F ST ) are similar or higher compared with those among wild populations (among-wild F ST ) (Li et al 2005;Lauterbach et al 2012;Yokogawa et al 2013;Miao et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Greater attention should also be paid to seed dormancy mechanisms. Miao et al (2015) found that individuals established by seed propagation had greater genetic diversity and contained more unique alleles than those that were vegetatively propagated. Similarly, Yang et al (2011) reported that the former tended to have greater numbers of prosperous roots, straighter trunks and stronger disease resistance than the latter.…”
Section: Figurementioning
confidence: 99%
“…In summary, the two natural T. yunnanensis populations investigated in this study were characterized by low genetic diversity following a population bottleneck, weak but significant SGS, extremely low effective population size and high inbreeding. To effectively conserve the genetic diversity of this species to maintain the adaptive potential under changing environmental conditions, in situ and ex situ conservation should be implemented (Miao et al, 2015), especially for the actual breeding individuals (Ne). Moreover, increasing the Ne can not only promote the quantity of expected heterozygosity (Ht), but also decrease the degree of inbreeding within a population based on the equation Ht/Ho = [1 -l/(2Ne)] t = 1 -F given by Falconer (1989).…”
Section: Figurementioning
confidence: 99%
“…Subsequently, the effectiveness of taxol has been documented for the treatment of various cancers, inflammatory conditions, and Acquired Immune Deficiency Syndrome (Yan et al 2013;Yang et al 2017). As one of the most successful anticancer drugs derived from natural sources (Yang et al 2017), taxol has a huge and expanding market demand (Miao et al 2015). The bark and leaves of T. wallichiana are now used to produce taxol, and this is the reason for its exploitation (Thomas and Farjon 2011;Uniyal 2013).…”
Section: Introductionmentioning
confidence: 99%